خصائصِ نبوی کے فقہی پہلو؛ ایک تحقیقی جائزہ: The Jurisprudential Aspects of Prophetic Characteristics; A Research Review - Razaq, Dr. Abdur; Dr. Iftikhar Alam (Al-Amīr Research Journal for Islamic Studies, 2025)
This paper explores the jurisprudential dimensions of the Prophet Muhammad’s (ﷺ) exclusive characteristics (Khaṣā’iṣ al-Nabawiyyah) which distinguish him from the rest of humanity and even other prophets. These characteristics include certain legal exemptions, unique obligations, and privileges that hold special significance in Islamic jurisprudence (fiqh). The study analyzes these aspects by referencing primary sources of Islamic law, including the Qur’an, Hadith, classical jurisprudential texts and works of scholars such as Imam al-Shafi‘i, al-Suyuti, Ibn Qudāmah and al-Shātibī. Key jurisprudential features examined include the Prophet’s ﷺ allowance for more than four marriages, the prohibition of receiving zakāh and alms, the obligation of night prayer (tahajjud) specifically upon him, the exclusive right to receive a portion of war booty (khums) and the distinctive legal rulings regarding his wives. The paper also discusses how these characteristics impacted the development of uṣūl al-fiqh (principles of jurisprudence), particularly the differentiation between general legal rulings and those exclusive to the Prophet ﷺ. The study further explores the implications of khaṣā’iṣ in modern legal and ethical discourse, suggesting that an understanding of these unique rulings can contribute to contemporary discussions on leadership, moral authority and the application of Islamic law in pluralistic contexts. Contemporary scholars such as Dr. Yusuf al-Qaradawi and Dr. Muhammad Ammar Khalid are also referenced for their insights into the relevance of these prophetic characteristics today. By offering a detailed analytical review of the khaṣā’iṣ al-nabawiyyah from a jurisprudential perspective, this research highlights their significance in shaping Islamic legal theory and ethical frameworks, while emphasizing the enduring legacy of the Prophet Muhammad’s ﷺ exemplary life in both classical and modern contexts.